From Kitchen to Clinic: A PRISMA-Based Systematic Review of Culinary-Induced Food Poisoning in Mass Feeding Programs and Its Mitigation in Cookery Science - Diyan Putranto; Marhanani Tri Astuti; Fransiscus Amonio Halawa (Sekolah Tinggi Manajemen Pariwisata dan Logistik Lentera Mondial, 2026)
Background: The Indonesian Makan Bergizi Gratis (MBG) program aims to combat child malnutrition through mass school feeding. However, transitioning from domestic to industrial-scale production introduces significant